Experimental and simulation studies on the phase behaviour for gas hydrates in a CO2 rich gas dominant multiphase pipeline system - Sayani, J.K.S. (John Wiley and Sons Inc, 2021)
In this work, an experimental and modelling study is performed to identify the phase behaviour of gas hydrates formation for a high CO2 content natural gas system and multiphase gas dominant system. Further, CSMGem, PVTSim, and Aspen HYSYS software packages are used to verify the prediction capabilities for gas hydrates formation conditions. Initially, thermodynamic equilibrium conditions are obtained using CSMGem, PVTSim, and Aspen HYSYS. Then, these results are validated and compared to the experimental work to verify the accuracy in predicting hydrate formation conditions. An experimental study is performed in the pressure range of 2â7Â MPa for a pure system and multiphase system with the gas composition of carbon dioxide (70) + methane (26) + ethane (2) + propane (1) + butane (1). The results show that the PVTSim software package shows the best accuracy with 99.9 for the pure system and 99.88 for the multiphase system. Â© 2021 Canadian Society for Chemical Engineering.